Inside Cover: Integrin‐Targeting Knottin Peptide–Drug Conjugates Are Potent Inhibitors of Tumor Cell Proliferation (Angew. Chem. Int. Ed. 34/2016). Issue 34 (20th June 2016) - Cox, Nick; Kintzing, James R.; Smith, Mark; Grant, Gerald A.; Cochran, Jennifer R.
Abstract : A knottin miniprotein first isolated from the seeds of the squirting cucumber has been engineered to bind selectively to tumor‐associated integrin receptors. In their Communication onpage 9894 ff., J. R. Cochran and co‐workers describe a knottin–gemcitabine conjugate that is over 40‐times smaller than an antibody–drug conjugate. This approach for targeted drug delivery offers an alternative strategy for the treatment of resistant tumors, such as brain or pancreatic cancer.